Internet of Things Based Advanced Telematics System For Electric Vehicles - Rathore, Arvindsingh (International Journal of Computer Sciences and Engineering, 2018)
The Internet of Things (IoT) will break newfangled ground for automobile manufacturers by introducing entirely new layers to the traditional concept of a car. Traditional LCD/LED dashboard displays have a constraint of space i.e. the data display is restricted exclusively to the drivers which make it infeasible for other concerned people to view and know about the various parameters of the vehicle. IoT along with cloud computing will help to store the sensor values and other crucial data on encrypted cloud servers which can help set up a telematics solution along with a data acquisition system accessible from anywhere in the world.